Hybrid Learning Lectures for Achieving Arabic Language Competence in the Free Curriculum Frame for Independent Learning (MBKM) at Zainul Hasan Islamic University Genggong Kraksaan Probolinggo - Ainur Rofiq Sofa; Abd Aziz; Muhammad Ichsan (CV. Ulil Albab Corp, 2022)
This article examines the Hybrid Learning system, the advantages and disadvantages of offline and online lectures in achieving basic competence in the Arabic language curriculum at the Zainul Hasan Genggong Kraksaan Islamic University Probolinggo. The purpose of this article is to find out what are the advantages and disadvantages of offline and online lectures. As we know, there are two lecture systems currently being implemented, namely the Hybrid Learning system or in other words online (within the network) and the offline system (outside the network). Of course, this Hybrid Learning system has similarities and differences, as well as the strengths and weaknesses both in the lecture process, as well as the effectiveness to be achieved, this will also affect the achievement of the basic competencies applied. This study uses a qualitative method with a descriptive approach based on field facts to determine the advantages and disadvantages of the Hybrid Learning system, offline and online lectures in achieving basic competencies in the Arabic curriculum. The results of the study and discussion show that there are data obtained in the field that offline and online lectures have advantages and disadvantages both in terms of methods, media, and the lecture process. And regarding this matter, both offline and online lectures do not guarantee that basic competencies in the MBKB curriculum frame in higher education institutions, especially the Zaiul Hasan Genggong Kraksaan Probolinggo Islamic University campus, can be fully achieved to the maximum according to institutional targets.